2015
DOI: 10.1016/j.appet.2015.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of thylakoid-rich spinach extract reduces hunger, increases satiety and reduces cravings for palatable food in overweight women

Abstract: Green-plant membranes, thylakoids, have previously been found to increase postprandial release of the satiety hormone GLP-1, implicated in reward signaling. The purpose of this study was to investigate how treatment with a single dose of thylakoids before breakfast affects homeostatic as well as hedonic hunger, measured as wanting and liking for palatable food (VAS). We also examined whether treatment effects were correlated to scores for eating behavior. Compared to placebo, intake of thylakoids significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 51 publications
(71 reference statements)
0
34
0
Order By: Relevance
“…32) For preparation of thylakoid-rich spinach extract, Appethyl ® , reagents containing these metals are not used. 12) Thus, we speculate that these metals in the thylakoid-rich spinach extract are derived from spinach itself. However, it is possible that content of metals in other thylakoid-rich spinach extract preparations may differ.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…32) For preparation of thylakoid-rich spinach extract, Appethyl ® , reagents containing these metals are not used. 12) Thus, we speculate that these metals in the thylakoid-rich spinach extract are derived from spinach itself. However, it is possible that content of metals in other thylakoid-rich spinach extract preparations may differ.…”
Section: Discussionmentioning
confidence: 85%
“…Thylakoid-rich spinach extract, a dietary supplement, is commonly obtained from baby spinach leaves using the pH method followed by drum drying, 12) and is being used for weight loss in Japan, as well as the U.S.A. and Europe. Clinical studies have demonstrated that thylakoid-rich spinach extract suppresses subjective hunger, promote body weight loss, and reduce low density lipoprotein cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a significant decrease in appetite and increase in hunger was seen by P. vulgaris (with dose of 100 mg/day; Spadafranca et al, ), C. fimbriata (with dose of 1,000 mg/day; Kuriyan et al, ), spinach (with dose of 5,000 mg/day; Rebello et al, , Stenblom, Egecioglu, Landin‐olsson, & Erlanson‐albertsson, ), flaxseed (with dose of 2,500 mg/day; Ibrugger, Kristensen, Mikkelsen, & Astrup, ), fenugreek (with dose of 8,000 mg/day; Mathern, Raatz, Thomas, & Slavin, ), G. cambogia (with dose of 1,000 mg/day; Mayer et al, , Preuss et al, ), green coffee (Roshan, Nikpayam, Sedaghat, & Sohrab, ), and the combination simplicifolia , asiatica , Taraxacum officinale , Cynara Scolymus , Paullina Sorbilis , Alga Klamath (Rondanelli, Klersy, Iadarola, Monteferrario, & Opizzi, ), and a combination of G. cambogia and Amorphophallus konjac (Vasques et al, ; Figure ). Some other articles have shown that Gundelia tournefortii (Hajizadeh‐Sharafabad, Alizadeh, Mohammadzadeh, Alizadeh‐Salteh, & Kheirouri, ), Coleus forskohlii (Loftus et al, ), N. sativa (Mahdavi et al, ), Garcinia atroviridis (Roongpisuthipong, Kantawan, & Roongpisuthipong, ), C. fimbriata (Kuriyan et al, ), a combination of ephedra and caffeine (Hackman et al, ) as well as a combination of walnut and flaxseed (Wu et al, ) significantly reduces energy intake (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…, spinach (with dose of 5,000 mg/day;Rebello et al, 2015, Stenblom, Egecioglu, Landin-olsson, & Erlanson-albertsson, 2015, flaxseed (with dose of…”
mentioning
confidence: 99%
“…By interacting with lipids and delaying fat digestion, thylakoid membranes promote the release of hormones that mediate satiety [90]. Studies investigating the effects of thylakoids (Appethyl™) on eating behavior have demonstrated increases in perceptions of satiety [91, 92], and a reduction in body weight [93]. Additionally, two studies demonstrated a decrease in the craving for sweet foods and chocolate among women in the overweight or obese body mass index range, measured subjectively [93, 94].…”
Section: Targeting Reward Mechanismsmentioning
confidence: 99%